Effects of different secondary metabolite profiles in plant defense syndromes on specialist and generalist herbivores. Issue 2 (28th April 2016) - Okamura, Yu; Sawada, Yuji; Hirai, Masami Yokota; Murakami, Masashi
Abstract: Plants defend themselves against herbivores not only by a single trait but also by diversified multiple defense strategies. It remains unclear how these multiple defense mechanisms are effectively organized against herbivores. In this study, we focused on Brassicaceae plants, which have one of the most diversified secondary metabolites, glucosinolates (GSLs), as a defense against herbivores. By analyzing various defense traits including GSL profiles among 12 species (11 genera) of Brassicaceae plants, it is revealed that their defense strategies can be divided into three categories as multiple defenses. The GSL profiles differed between these three categories: (i) high nutritional level with long‐chain aliphatic GSLs; (ii) low nutritional level and high physical defenses with short‐chain aliphatic GSLs; and (iii) high nutritional level and low defense. The feeding experiment was conducted using two types of herbivores, Pieris rapae (Lepidoptera: Pieridae) as a specialist herbivore and the Eri silkmoth Samia cynthia ricini (Lepidoptera: Saturniidae) as a generalist, to assess the ability of each plant in multiple defense strategy. It was observed that the Eri silkmoth's performance differed according to which defense strategy it was exposed to. However, the growth rate of P. rapae did not vary among the three categories of defense strategy. These results suggest that the diversified defense strategies of Brassicaceae species have evolved to cope with diversified herbivores. Abstract : In this study, we focused on Brassicaceae plants that have one of the most diversified secondary metabolites, glucosinolates (GSLs), as a defense against herbivores. It was observed that the Eri silkmoth's performance differed according to which defense strategy it was exposed to, but the growth rate of P . rapae did not vary against the same defense strategies. These results suggest that the diversified defense strategies of Brassicaceae species have evolved to cope with diversified herbivores.